What is ACWC (ASEAN Commission on the Promotion and Protection of the Rights of Women and Children)? A Study on the International Policy Instruments - Wahyuningrum, Yuyun (Yayasan Jurnal Perempuan, 2015)
ASEAN has established a commission specialised in advancing and protection rights of women and children in Hanoi Vietnam on 7 April 2010. This commission is called ACWC (ASEAN Commission on the Promotion and Protection of the Rights of Women and Children). This paper investigates and narrates its history, challenges and hindrance being faced to advance human rights. It argues that despite all the obstacles, ACWC has crucial potential to increase women and children participation as well as state and community to advance human rights in ASEAN.